Documental audiovisual trayectoria laboral de los graduados de comunicación social UPS. - Carvajal Mantilla, Diego Sebastián (2018)
The practice of communication has acquired an important place in the national context, communicators play a significant role in the national development and an important part of the professionals that are now national referents of the communication have been formed academically in Universidad Politécnica Salesiana, that is why is necessary to study the professional path of the communicators that graduated from UPS. The following investigation is about the study of the professional path of the communication graduates from UPS, the management models that have been incorporated in their professional life and the visibility of punctual cases of success, making them referents from the students and future students from UPS. The research process whose methodological approach has been based on the application of the in-depth interview has been oriented towards the collection of information that allows knowing the professional development of the graduates so that the results of this process are reflected in an audiovisual documentary that follows the quality standards for its diffusion and to be implemented as an input and strengthen the corporate image of the Universidad Politécnica Salesiana, campus Quito and in particular the Career of Social Communication.